Investigating Fishing Vessel Hydrodynamics by Using EFD and CFD Tools, with Focus on Total Ship Resistance and Its Components - Oyuela, Sebastian (2024)
The aim of this work is to gain a better understanding of the hydrodynamics of a typical Argentinian fishing vessel in calm water. It is focused on the evaluation of total ship resistance and its components for different draughts. The 1978 ITTC Power Prediction method is used to predict total ship resistance from experiments carried out at the University of Buenos Aires towing tank. To conduct a more detailed evaluation of the flow around this hull, numerical studies at model scale are carried out with the open-source code OpenFOAM V10 and validated against experimental results. The Reynolds-Averaged Navier–Stokes (RANS) method together with Volume of Fluid (VOF) are used for the numerical procedure. The validated CFD model not only can provide more detailed information about the ship’s hydrodynamics than the EFD results but also allows for the exploration of the improvement in ship power prediction by using combined CFD-EFD methodologies. This work numerically calculates the form factor by using a double-body configuration and discusses the possibility of combining EFD results with this CFD form factor in order to improve total force prediction for this kind of ships.